2016
DOI: 10.3892/mmr.2016.4852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the tumor suppressor PTEN on the pathogenesis of idiopathic pulmonary fibrosis in Chinese patients

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by progressive interstitial fibrosis, and is associated with a fatal outcome. The critical pathological mechanisms underlying IPF are largely unknown; however, accumulating evidence has indicated similarities between IPF and cancer. Therefore, the present study examined the expression levels of the tumor suppressor phosphatase and tensin homolog deleted on chromosome 10 (PTEN) in Chinese patients with IPF, using an enzyme‑linked immunosorbent assay. To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In addition, TGF-b-induced activation of fibroblasts into α-SMA-positive myofibroblasts in order to synthesize type-1 collagen is a vital event in allergic asthma (22). In line with our results, a prior study also observed that PTEN overexpression resulted in a reduced expression of α-SMA (25).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, TGF-b-induced activation of fibroblasts into α-SMA-positive myofibroblasts in order to synthesize type-1 collagen is a vital event in allergic asthma (22). In line with our results, a prior study also observed that PTEN overexpression resulted in a reduced expression of α-SMA (25).…”
Section: Discussionsupporting
confidence: 91%
“…According to Xie et al [50], PTEN overexpression decreases signalling via the PI3K/AKT and TGF β/Smad3 pathways in IPF and inhibits TGF β1 mediated myofibroblast differentiation. An increased TGF β in OSF can reduce PTEN levels allowing for AKT activity and consequently prolonged survival of fibroblasts and increased ECM production and fibrosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although SLPI null animals with overexpressed MMP-2 expression show longer wound recovery and enhanced localized scarring, they do not develop PF [123]. The tumor suppressor phosphatase and tensin homolog deleted on chromosome 10 (PTEN) inhibits the expression levels of several crucial proteins in TGF-β1-induced fibrosis, including MMP-2, MMP-9 and α-SMA by blocking the phosphatidylinositol 3-kinase/Akt and TGF-β1/SMAD3 pathways, reducing fibroblast-to-myofibroblast transition (FMT) [124].…”
Section: Mmp-2mentioning
confidence: 99%